Sex, Gender and Age Differences in Treatment Allocation and Survival of Patients With Metastatic Pancreatic Cancer: A Nationwide Study - Pijnappel, Esther N.; Schuurman, Melinda; Wagner, Anna D.; de Vos-Geelen, Judith; Geest, Lydia G. M. van der; de Groot, Jan-Willem B.; Koerkamp, Bas Groot; de Hingh, Ignace H. J. T.; Homs, Marjolein Y. V.; Creemers, Geert-Jan; Cirkel, Geert A.; van Santvoort, Hjalmar C.; et al. (Frontiers in Oncology, 2022)
Background: Biological sex, gender and age have an impact on the incidence and outcome in patients with metastatic pancreatic cancer. The aim of this study is to investigate whether biological sex, gender and age are associated with treatment allocation and overall survival (OS) of patients with metastatic pancreatic cancer in a nationwide cohort. Methods: Patients with synchronous metastatic pancreatic cancer diagnosed between 2015 and 2019 were selected from the Netherlands Cancer Registry (NCR). The association between biological sex and the probability of receiving systemic treatment were examined with multivariable logistic regression analyses. Kaplan Meier analyses with log-rank test were used to describe OS. Results: A total of 7470 patients with metastatic pancreatic cancer were included in this study. Fourty-eight percent of patients were women. Women received less often systemic treatment (26% vs. 28%, P=0.03), as compared to men. Multivariable logistic regression analyses with adjustment for confounders showed that women ≤55 years of age, received more often systemic treatment (OR 1.82, 95% CI 1.24-2.68) compared to men of the same age group. In contrast, women at >55 years of age had a comparable probability to receive systemic treatment compared to men of the same age groups. After adjustment for confounders, women had longer OS compared to men (HR 0.91, 95% CI 0.87-0.96). Conclusion: This study found that women in general had a lower probability of receiving systemic treatment compared to men, but this can mainly be explained by age differences. Women had better OS compared to men after adjustment for confounders.